Cost-Effectiveness of Endovascular Treatment in Large Vessel Occlusion Stroke With Mild Prestroke Disability: Results From the HERMES Collaboration. Issue 1 (6th December 2022) - Ospel, Johanna M.; Kunz, Wolfgang G.; McDonough, Rosalie V.; van Zwam, Wim; Pinckaers, Floor; Saver, Jeffrey L.; Hill, Michael D.; Demchuk, Andrew M.; Jovin, Tudor G.; Mitchell, Peter; Campbell, Bruce C.V.; White, Phil; et al.
Abstract : Background: The clinical and economic benefit of endovascular treatment (EVT) in addition to best medical management in patients with stroke with mild preexisting symptoms/disability is not well studied. We aimed to investigate cost-effectiveness of EVT in patients with large vessel occlusion and mild prestroke symptoms/disability, defined as a modified Rankin Scale score of 1 or 2. Methods: Data are from the HERMES collaboration (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials), which pooled patient-level data from 7 large, randomized EVT trials. We used a decision model consisting of a short-run model to analyze costs and functional outcomes within 90 days after the index stroke and a long-run Markov state transition model (cycle length of 12 months) to estimate expected lifetime costs and outcomes from a health care and a societal perspective. Incremental cost-effectiveness ratio and net monetary benefits were calculated, and a probabilistic sensitivity analysis was performed. Results: EVT in addition to best medical management resulted in lifetime cost savings of 2821 (health care perspective) or 5378 (societal perspective) and an increment of 1.27 quality-adjusted life years compared with best medical management alone, indicating dominance of additional EVT as a treatment strategy. The net monetary benefits were higher for EVT in addition to best medical management compared with best medical management alone both at the higher (100 000/quality-adjusted life years) and lower (50 000/quality-adjusted life years) willingness to pay thresholds. Probabilistic sensitivity analysis showed decreased costs and an increase in quality-adjusted life years for additional EVT compared with best medical management only. Conclusions: From a health-economic standpoint, EVT in addition to best medical management should be the preferred strategy in patients with acute ischemic stroke with large vessel occlusion and mild prestroke symptoms/disability.